2020
DOI: 10.1063/1.5127970
|View full text |Cite
|
Sign up to set email alerts
|

Study of core plasma rotation characteristics of RF-heated H-mode discharges on experimental advanced superconducting tokamak

Abstract: RF-heated H-mode plasmas are readily achieved with lower hybrid current drive and ICRF heating on experimental advanced superconducting tokamak (EAST). Characteristics of H-mode plasma rotation are studied, including the behaviors for non-stationary and stationary H-mode discharges. Experimental results indicate that substantial co-current core rotation increment is observed at L-H transition. For non-stationary discharges with multiple L-H transitions, central plasma rotation varies as the plasma enters and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Here we have demonstrated that any non-zero rotation in DEMO can be robustly identified with CTS, at least down to levels of v i ∼ 20 km s −1 . This is at the low end of the range in intrinsic rotation velocities inferred in existing devices (∼10-60 km s −1 ) for Ohmic or wave-heated plasmas with no external momentum input [24,26,27,[46][47][48]. As demonstrated by figure 8, inference of v i would greatly benefit from the high frequency resolution afforded by a digitizerbased CTS system.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Here we have demonstrated that any non-zero rotation in DEMO can be robustly identified with CTS, at least down to levels of v i ∼ 20 km s −1 . This is at the low end of the range in intrinsic rotation velocities inferred in existing devices (∼10-60 km s −1 ) for Ohmic or wave-heated plasmas with no external momentum input [24,26,27,[46][47][48]. As demonstrated by figure 8, inference of v i would greatly benefit from the high frequency resolution afforded by a digitizerbased CTS system.…”
Section: Discussionmentioning
confidence: 86%
“…No information on net toroidal plasma rotation v i is available in the adopted equilibrium, nor is any heating or current drive from neutral beam injection (NBI) envisaged in the adopted plasma scenario or in the current plans for the baseline heating system of DEMO in general [23]. Some intrinsic turbulence-driven rotation might be expected in DEMO even in the absence of auxuliary torque input [24][25][26][27]; however, since this is challenging to predict quantitatively, we have here generally assumed v i = 0 when generating or inverting the synthetic spectra. We will revisit this assumption on v i in section 3.3.…”
Section: Plasma Scenario and Raytracingmentioning
confidence: 99%
“…Research shows that intrinsic plasma rotation is very sensitive to magnetic field configuration, plasma density, current density profile and ion temperature [7,8]. The experimental results of intrinsic rotation in JET [9], Alcator C-mod [5], Tore Supra [10], DIII-D [11], JT-60U [12] and EAST [13] suggest that the intrinsic rotation was strongly correlated with plasma pressure gradient or stored energy in H-mode plasma. Researches on KSTAR also shows the dependency of intrinsic rotation on plasma density and collisionality [14].…”
Section: Introductionmentioning
confidence: 97%
“…While NBIs have been a popular tool to modify plasma rotations, applications of RF (Radio Frequency) wave heating systems such as ICRF (Ion Cyclotron Range of Frequency), LHCD (Lower Hybrid Current Drive), and ECRH (Electron Cyclotron Resonance Heating), have also proven to modify plasma rotations, thus can affect RS profiles and their magnitudes. Some recent publications from EAST experiments on intrinsic rotations with various RF heating tools can be found in [25][26][27][28][29]. Knowing such diverse rotation responses to RF waves, it is reasonable to assume that seeminglybalanced rotations can be attained by combined application of NBIs and RF waves as done during the 2019 EAST campaign.…”
Section: Introductionmentioning
confidence: 99%